2013
DOI: 10.1186/1752-4458-7-7
|View full text |Cite
|
Sign up to set email alerts
|

Core concepts of human rights and inclusion of vulnerable groups in the mental health policies of Malawi, Namibia, and Sudan

Abstract: BackgroundOne of the most crucial steps towards delivering judicious and comprehensive mental health care is the formulation of a policy and plan that will navigate mental health systems. For policy-makers, the challenges of a high-quality mental health system are considerable: the provision of mental health services to all who need them, in an equitable way, in a mode that promotes human rights and health outcomes.MethodEquiFrame, a novel policy analysis framework, was used to evaluate the mental health polic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…This study applied a socially vulnerable group demand index (hereinafter SDI) to calculate the accessibility level of various green parks in Dhaka to vulnerable social classes. Vulnerable groups were defined as social groups that possess minimal assets and thus experience high relative dangers of hardship and untimely mortality [67]. Vulnerability also refers to a person's social status and living standard other than physical conditions.…”
Section: Methodological Approachmentioning
confidence: 99%
“…This study applied a socially vulnerable group demand index (hereinafter SDI) to calculate the accessibility level of various green parks in Dhaka to vulnerable social classes. Vulnerable groups were defined as social groups that possess minimal assets and thus experience high relative dangers of hardship and untimely mortality [67]. Vulnerability also refers to a person's social status and living standard other than physical conditions.…”
Section: Methodological Approachmentioning
confidence: 99%
“…For example, a recent study to explore mental disorder and its association with sexual risk behaviors and HIV found that more women than men experienced higher rates of depression, psychological distress, alcohol abuse all associated with increased sexual risk behaviors, rape and violence by partners and non-partners. [ 28 ] Other findings have indicated that more women in the general population experienced severe mental disorders combined with HIV and admission to hospital. Although these discoveries lend credence to a correlation between trauma and behavior, the lack of crucial information pertaining to whether the disorder preceded or resulted from the traumatic event is crucial in order to reach a thorough understanding and to treat appropriately.…”
Section: Gender and Mental Health In Ugandamentioning
confidence: 99%
“…First, people with disabilities and people with ID were included as vulnerable groups, and not all twelve vulnerable groups used in the original EquiFrame were included in the research. Second, although the initial EquiFrame tool was used specifically for analyzing health policy (Eide et al, ; Mannan et al, ; Schneider et al, ), it has also been successfully applied beyond health policy with international policy in the form of the UNCRPD (Mannan et al, ), disability policy (O'Dowd et al, ), and orthopedic technical services (Van Rooy et al, ). EquiFrame's reach can therefore extend beyond health policy to other guiding or accompanying documents (Van Rooy et al, ).…”
Section: Methodsmentioning
confidence: 99%